The crosstalk between microbial sensors ELMO1 and NOD2 shape intestinal immune responses - ruhme, bridget; Treml, Jack (Midwestern Journal of Undergraduate Sciences, 2024)
Microbial sensors are integral to maintaining cellular homeostasis and orchestrating immune responses within the intestinal environment. The mechanisms contributing to differential immune responses and their link to inflammatory bowel diseases (IBD) are not yet fully understood. IBD is an umbrella term used to describe disorders that cause chronic inflammation of the gastrointestinal tract. This review explores The crosstalk between microbial sensors ELMO1 and NOD2 shape intestinal immune responses during enteric infections of AIEC-LF82 and Salmonella published in the February 2023 Virulence Journal by Aditi Sharma et al.